2018
DOI: 10.1016/j.idairyj.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive oil in dairy cow diets on the fatty acid profile and sensory characteristics of cheese

Abstract: Effect of olive oil in dairy cow diets on the fatty acid profile and sensory characteristics of cheese

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 33 publications
(35 reference statements)
3
33
0
Order By: Relevance
“…Similarly, Bernard et al [23] fed dairy goats with soybeans and did not observe changes in abundance of ACACA at both mammary gland and adipose tissue levels. Stable abundance of ACACA in this study, could partly explain, the lack of differences observed in the proportions of C4:0, C6:0, and C16:0 in milk reported in our companion paper [1]. Synthesis of short-chain FA and palmitic acid is mainly regulated by the action of this enzyme, which would be a critical point in the de novo synthesis [24,25].…”
Section: Effects Of Oo and Hvo On Lipid Metabolism-related Genes In Mscsupporting
confidence: 43%
See 4 more Smart Citations
“…Similarly, Bernard et al [23] fed dairy goats with soybeans and did not observe changes in abundance of ACACA at both mammary gland and adipose tissue levels. Stable abundance of ACACA in this study, could partly explain, the lack of differences observed in the proportions of C4:0, C6:0, and C16:0 in milk reported in our companion paper [1]. Synthesis of short-chain FA and palmitic acid is mainly regulated by the action of this enzyme, which would be a critical point in the de novo synthesis [24,25].…”
Section: Effects Of Oo and Hvo On Lipid Metabolism-related Genes In Mscsupporting
confidence: 43%
“…C18:1 trans-10 has been reported to affect (anti-lipogenic effect) the abundance of genes involved in lipid metabolism at the mammary gland level [18]. This trans isomer was found in milk from OO, therefore, results in plasma FA partly explain the decrease in milk fat yield observed with OO reported previously [1].…”
Section: Fatty Acid Profile In Plasmamentioning
confidence: 80%
See 3 more Smart Citations